If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x * -3) + 3 = 24 Reorder the terms for easier multiplication: 7(2 * -3x) + 3 = 24 Multiply 2 * -3 7(-6x) + 3 = 24 Remove parenthesis around (-6x) 7 * -6x + 3 = 24 Multiply 7 * -6 -42x + 3 = 24 Reorder the terms: 3 + -42x = 24 Solving 3 + -42x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -42x = 24 + -3 Combine like terms: 3 + -3 = 0 0 + -42x = 24 + -3 -42x = 24 + -3 Combine like terms: 24 + -3 = 21 -42x = 21 Divide each side by '-42'. x = -0.5 Simplifying x = -0.5
| 11=20x+8 | | 2+8=34 | | y=-5t^2+14t+3 | | w=-275(2t-1000) | | (1-m)x^2-2x+m+1=0 | | f(t)=3t-1 | | w=1000+-550t | | (18x-8)2=4x+16 | | 6x^2-x-37=0 | | 4x^2-14x+116=y | | lnx=(x+6)-ln(x-4) | | w=-2750+1100 | | w=-275+1100 | | Y=5x^2+3x-2 | | w^2+3w=54 | | 6d+12d=10d+35 | | Y=2x^2+17x+8 | | -13p=-3 | | Y=4x^2+11x-20 | | 4x+32=60 | | -15p=-3 | | 2x-1=9*x-6 | | Y=3x^2-14x-5 | | 14+(-80)= | | Y=x^2-144 | | 2.25-3x+x^2=18 | | 12x+11y=-77 | | 6a+9b=21 | | 3y=18x+24 | | 8x-2=3x-11 | | -3x+2.25+x^2=20.25 | | 2a+2b=10 |